La métamorphose du regard de Polypheme dans la peinture de Marij Pregelj (1913-1967) - Mikuž, Jure (Ars et humanitas, 2015)
In 1949-1951 Marij Pregelj, one of the most interesting Slovenian modernist painters, illustrated his version of Homer's Iliad and Odsssey. His illustrations were presented in the time of socialist realist aesthetics announce a reintegration of Slovenian art into the global (Western) context. Among the illustrations is the figure of Cyclops devouring Odysseus' comrades. The image of the one-eyed giant Polyphemus is one which concerned Pregelj all his life: the painter, whose vocation is most dependent on the gaze, can show one eye in profile. And the profiles of others' faces and of his own face interested Pregelj his whole life through. Not only people but also objects were one-eyed: the rosette of a cathedral, which changes into a human figure, a washing machine door, a meat grinder's orifice, a blind "windeye" or window, and so on. The themes of his final two paintings, which he, already more than a year before his boding senseless death at the age of 54, executed but did not complete, are Polyphemus and the Portrait of His Son Vasko. In the first, blood flows from the pricked-out eye towards a stylized camera, in the second, the gaze of the son, an enthusiastic filmmaker, extends to the camera that will displace the father's brush.
Keywords: modern Slovenian painting; Pregelj, Marij, 1913-1967; myths; Polifem; Polyphemus; miti; mythology; slovensko slikarstvo; moderno slikarstvo